Effect of lockdown due to COVID-19 pandemic on mental health of final year students of Maharashtra - Gupta, Roli R.; Vaishnao, Lohit S.; Shinde, Shivani; Singh, Ishani; Mishra, Tanaya; Sharma, Khushboo (International Journal Of Community Medicine And Public Health, 2020)
Background: A pandemic is the worldwide spread of a new disease and currently COVID‑19 has become a major medical crisis. The worldwide rapid increase of infected cases has created a sense of uncertainty and anxiety about the situations and upcoming exams period. It also leads to stress amongst the students. Objectives of the study was to evaluate and analyse the prevalence of depression, anxiety and stress among final year students of Maharashtra using DASS-21. Methods: It was an online survey which was conducted using Google Forms with link sent using Whatsapp. A standard DASS-21 questionnaire was used for the study. The survey questionnaire would take around 3-4 min to complete. Total 324 responses were received by the stipulated time. Results: The study showed that the engineering final year students are more depressed than others. 34 engineering and 26 medical students were suffering from anxiety. The relationship between anxiety level and course was statistically significant. On depression scale 47% participants were suffering from mild to moderate stress. Conclusions: Index survey suggested that the pandemic affected the preparation of the respondents to a great extent and affected their mental status negatively.